Inactivated vaccine with glycyrrhizic acid adjuvant elicits potent innate and adaptive immune responses against foot-and-mouth disease - Shin, Seokwon; Kim, Hyeong Won; Ko, Mi-Kyeong; Park, So Hui; Kim, Su-Mi; Park, Jong-Hyeon; Lee, Min Ja (Frontiers in Microbiology, 2023)
Foot-and-mouth disease (FMD) is an extremely contagious viral disease that is fatal to young animals and is a major threat to the agricultural economy by reducing production and limiting the movement of livestock. The currently commercially-available FMD vaccine is prepared using an inactivated viral antigen in an oil emulsion, with aluminum hydroxide [Al(OH)3] as an adjuvant. However, oil emulsion-based options possess limitations including slow increases in antibody titers (up to levels adequate for defense against viral infection) and risks of local reactions at the vaccination site. Further, Al(OH)3 only induces a T helper 2 (Th2) cell response. Therefore, novel adjuvants that can address these limitations are urgently needed. Glycyrrhizic acid (extracted from licorice roots) is a triterpenoid saponin and has great advantages in terms of price and availability. To address the limitations of the currently used commercial FMD vaccine, we added glycyrrhizic acid as an adjuvant (immunostimulant) to the FMD bivalent (O PA2+A YC) vaccine. We then evaluated its efficacy in promoting both innate and adaptive (cellular and humoral) immune reactions in vitro [using murine peritoneal exudate cells (PECs) and porcine peripheral blood mononuclear cells (PBMCs)] and in vivo (using mice and pigs). Glycyrrhizic acid has been revealed to induce an innate immune response and enhance early, mid-, and long-term immunity. The studied bivalent vaccine with glycyrrhizic acid increased the expression of immunoregulatory genes such as pattern-recognition receptors (PRRs), cytokines, transcription factors, and co-stimulatory molecules. Collectively, glycyrrhizic acid could have utility as a novel vaccine adjuvant that can address the limitations of commercialized FMD vaccines by inducing potent innate and adaptive immune responses.